Enclosed aisle effect on cooling efficiency in small scale data center. (2017) - Lyu, Chao; Chen, Guangming; Ye, Shuiquan; Liu, Yueqin
Abstract: Taking actual computer room of small scale data center in project as an example, airflow distribution of computer room in different aisle types were simulated, and temperature and velocity field were analyzed. An experiment was also carried out for the newly used computer room. The study shows that cold and hot air mix at two sides and top of free open cold and hot aisles, which reduces the utilization of cold air. Cooling effect of free open, semi-enclosed and full enclosed cold aisle turns better; and the effect of semi-enclosed cold aisle is obvious, which is recommended to use. Computer room's temperatures of full enclosed hot aisle are lower than that of full enclosed cold aisle. So the former has a slight advantage, but requires more aisle partitions and higher cost. When the heat quantity of computer room is small, the natural cooling capacity of outdoor air in winter can meet the cooling requirement. Test data also show that enclosed cold aisle can improve the cooling efficiency.